Public Sector Organization in Central and Eastern Europe: From Agencification to De-Agencification - Tiina RANDMA-LIIV; Vitalis NAKROŠIS; György HAJNAL (Transylvanian Review of Administrative Sciences, 2011)
The processes of transition and accession to the EU produced a fast expansion in the number of agencies and other public sector organizations in CEE. Between 1990 and 2004, many new organizations were established in order to implement new or reorganized functions of the democratic state, market economy and the EU member state. Agencies were created at a very high speed and with a larger scope than in most Western countries. Such a trend was counteracted by a major U-turn in the second half of the 2000s, when all studied CEE countries experienced a de-agencification process facilitated by the financial crisis and the aim to rationalize public sector organization. The studies in this special issue show that there is a considerable variation in terms of organizational autonomy and control, both across and within individual countries, and a clear domination of ex ante control over ex post control in the CEE region. Finally, politicization of agencies is identified as an important feature influencing their functioning in some CEE countries.